Studying the Problems of Attracting Attention in the Physical Education Lesson for the Preparatory Stasge from the Female Teachers Point of View (Medico Legal Update, 2020)
The lesson of physical education is more vulnerable to the problems of attracting attention as it is in awider area and includes freedom of movement and flexibility in dealing in the classroom and sometimesthe distraction in the physical education school increases due to the large number of female students, thusproviding the opportunity to practice such behavioral problems, since the practice of sports activity, especiallythe physical education lesson, is appropriate for free behavior and from it turns into an abnormal behavioras a result of being affected by the family circumstances to which the female students belong, Hence theimportance of this research shows that the problems of attracting attention If the professors, educators, andresearchers do not work with research to determine it, which leads to female students’ personal and socialmaladjustment in and outside the school, then when these problems are left without supervision, it may leadto their increase and the difficulty of dealing with them, In addition to the inability of female students toagree in the school, and therefore, a barrier between them and benefiting from the school’s educational andeducational services that achieve integrated and balanced growth for all aspects of personality, to qualifythem for the right citizenship in line with the goals of society, As for the research methodology, the researcherused the descriptive approach in the survey method to suit the nature of the research problem. As for theresearch sample, the research community was identified as physical education female teachers in Dhi QarGovernorate for the preparatory stage as shown in table (1) so the number of schools reached (50) schools,while the number Female teachers reached (235) Female teachers. As for the research findings, the mostimportant of them is the scale that was prepared by researchers as a tool to uncover problems of attractingattention in the lesson of physical education for the preparatory stage from the point of view of femaleteachers. They resort to attract the attention of others With negative behavior.